PENGARUH RASIO PROFITABILITAS TERHADAP HARGA SAHAM PADA PT BANK BCA TBK PERIODE 2016-2020 - Indri Astuti; Hadi Mulyo Wibowo; Rina Rupiah (Sekolah Tinggi Manajemen IMMI, 2022)
This research aims to find out whether the profitability ratio, namely Return On Asset (ROA), Return On Equity (ROE), Net Profit Margin (NPM) and Earning Per Share (EPS) has a simultaneous and quotient effect on prices shares in PT Bank BCA Tbk for the 2016-2020 period. The analytical techniques used in this study are classical assays and multiple linear regression. The population and sample in this study are the financial statements of Bank BCA Tbk registered with the OJK (Financial Services Authority) for 2016-2020. The data used is secondary data. The results of the test can be concluded that Return On Asset (ROA), Return On Equity (ROE), Net Profit Margin (NPM) and Earning Per Share (EPS) simultaneously and parsilan did not have a positive and negative effect and did not have a positive and negative effect. significant to the shares of PT Bank BCA Tbk for the period 2016-2020.Keywords: ROA, ROE, NPM, EPS, Share Price